Hourly Effect of Pretreatment With IV Antibiotics on Blood Culture Positivity Rate in Emergency Department Patients. (20th May 2019) - Rand, Kenneth H; Beal, Stacy G; Rivera, Kimberly; Allen, Brandon; Payton, Thomas; Lipori, Gloria P
Abstract: Although it is intuitive that antibiotics administered before obtaining a blood culture would reduce the likelihood of obtaining a positive culture, it is not clear exactly how rapidly and to what extent blood becomes sterile after administration of intravenous (IV) antibiotics. Using a large data set of patients admitted from the UFHealth Shands Adult Emergency Department (ED) between 2012 and 2016 (n = 25 686), we had the opportunity to more closely examine the effect of starting IV antibiotics before vs after obtaining blood cultures. We present data on the effect of pretreatment with IV antibiotics for both septic and nonseptic ED patients on the blood culture positivity rate on an hour-by-hour basis, as well as the effects on distribution of species recovered and the impact of antibiotic resistance in empiric treatment with antibiotics.